Complete mitochondrial genome of the Belligerent sculpin Megalocottus platycephalus (Cottoidei: Cottidae) - Balakirev, Evgeniy S. (Mitochondrial DNA B Resour, 2019)
The complete mitochondrial (mt) genome was sequenced in two specimens of the Belligerent sculpin Megalocottus platycephalus by high-throughput sequencing technology (Ion S5 platform). The sequences are 16,673 bp in size, and the gene arrangement, composition, and size are very similar to the other sculpin mt genomes published previously. Comparison of the two M. platycephalus mt genomes now obtained with other complete mt genomes available in GenBank reveals an affinity to the sculpin fishes from the genus Myoxocephalus. The intergeneric difference between the Megalocottus and Myoxocephalus is 0.0757 ± 0.0019, which is significantly less than the corresponding value, 0.1240 ± 0.0120, obtained previously for the sculpin fishes based on the COI barcoding marker.